PENGARUH JOB AUTONOMY DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DINAS PERDAGANGAN KOTA SEMARANG DENGAN SELF EFFICACY SEBAGAI VARIABEL MEDIASI - Puspita, Maya Shinta Rahma; Violinda, Qristin; Meiriyanti, Rita (Gapenas Publisher, 2025)
This study aims to determine the effect of job autonomy and work environment on employee performance with self-efficacy as a mediating variable. This study was conducted at the Semarang City Trade Office. The researcher used primary data obtained through the distribution of questionnaires via Google Forms and questionnaire sheets to employees of the Semarang City Trade Office. The population in this study consisted of employees of the Semarang City Trade Office. The sampling technique used was purposive sampling with a total of 154 respondents. The analysis tool used in this study was SmartPLS version 4.0. Data were collected using questionnaires and analyzed using SmartPLS version 4.0. The results of this study are that job autonomy has a positive and significant effect on employee performance, the work environment has a positive and significant effect on employee performance, self-efficacy has a positive and significant effect on employee performance, job autonomy has no significant effect on self-efficacy, the work environment has a positive and significant effect on self-efficacy, self-efficacy mediates the effect of job autonomy on employee performance, and self-efficacy mediates the effect of the work environment on employee performance